Autosomal dominant retinitis pigmentosa-associated gene PRPF8 is essential for hypoxia-induced mitophagy through regulating ULK1 mRNA splicing. Issue 10 (3rd October 2018) - Xu, Guang; Li, Ting; Chen, Jiayi; Li, Changyan; Zhao, Haixin; Yao, Chengcheng; Dong, Hua; Wen, Kaiqing; Wang, Kai; Zhao, Jie; Xia, Qing; Zhou, Tao; et al.
ABSTRACT: Aged and damaged mitochondria can be selectively degraded by specific autophagic elimination, termed mitophagy. Defects in mitophagy have been increasingly linked to several diseases including neurodegenerative diseases, metabolic diseases and other aging-related diseases. However, the molecular mechanisms of mitophagy are not fully understood. Here, we identify PRPF8 (pre-mRNA processing factor 8), a core component of the spliceosome, as an essential mediator in hypoxia-induced mitophagy from an RNAi screen based on a fluorescent mitophagy reporter, mt-Keima. Knockdown of PRPF8 significantly impairs mitophagosome formation and subsequent mitochondrial clearance through the aberrant mRNA splicing of ULK1, which mediates macroautophagy/autophagy initiation. Importantly, autosomal dominant retinitis pigmentosa (adRP)-associated PRPF8 mutant R2310K is defective in regulating mitophagy. Moreover, knockdown of other adRP-associated splicing factors, including PRPF6, PRPF31 and SNRNP200, also lead to ULK1 mRNA mis-splicing and mitophagy defects. Thus, these findings demonstrate that PRPF8 is essential for mitophagy and suggest that dysregulation of spliceosome-mediated mitophagy may contribute to pathogenesis of retinitis pigmentosa.